2018
DOI: 10.1097/md.0000000000010016
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery after surgery (ERAS) programs for esophagectomy protocol for a systematic review and meta-analysis

Abstract: Background:Esophageal cancer is one of the worst malignant digestive neoplasms with poor treatment outcomes. Esophagectomy plays an important role and offers a potential curable chance to these patients. However, esophagectomy with radical lymphadenectomy is known as one of the most invasive digestive surgeries which are associated with high morbidity and mortality. The enhanced recovery after surgery (ERAS) protocol is a patient-centered, surgeon-led system combining anesthesia, nursing, nutrition, and psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
1
23
0
3
Order By: Relevance
“…The importance of perioperative management is highlighted because esophageal cancer is the ninth most commonly diagnosed and the sixth most common cause of cancer-related neoplasms with a high perioperative risk of death (1). The best treatment option for these patients is esophagectomy as a curative approach; however, this procedure with radical lymphadenectomy is known as one of the most invasive digestive operations (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of perioperative management is highlighted because esophageal cancer is the ninth most commonly diagnosed and the sixth most common cause of cancer-related neoplasms with a high perioperative risk of death (1). The best treatment option for these patients is esophagectomy as a curative approach; however, this procedure with radical lymphadenectomy is known as one of the most invasive digestive operations (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of ERAS, or fast-track surgery, was introduced in 1997 by Dr. Henrik Kehlet [9], a gastrointestional surgeon who won 2014 Excellence in Research Award by the American Society of Anesthesiologists (ASA) for his outstanding contributions to anesthesiology by the creation of ERAS. A number of literatures, including clinical studies [10][11][12], reviews [6,13,14], and meta-analysis [4,15,16] demonstrated that compared with conventional treatment, implementation of ERAS protocol could be associated with reduced length of stay in hospital, decreased morbidity, attenuated stress, less in-hospital cost, and accelerated recovery in various types of surgery during perioperative period.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of ERAS, or fast-track surgery, was introduced in 1997 by Dr. Henrik Kehlet [11], a gastrointestional surgeon who won 2014 Excellence in Research Award by the American Society of Anesthesiologists (ASA) for his outstanding contributions to anesthesiology by the creation of ERAS. A number of literatures, including clinical studies [12][13][14], reviews [6,15,16], and meta-analysis [4,17,18] demonstrated that compared with conventional treatment, implementation of ERAS protocol could be associated with reduced length of stay in hospital, decreased morbidity, attenuated stress, less in-hospital cost, and accelerated recovery in various types of surgery during perioperative period.…”
Section: Discussionmentioning
confidence: 99%